Implementing Classroom Management on The History of Islamic Cultural Learning at TMI Putri Al-Amien Prenduan - Fina Marshella; Asep Maulana (IJIE International Journal of Islamic Education, 2022)
Improving education quality can be improved through the learning process that occurs directly in the classroom. TMI Al-Amien Prenduan is the first secondary further education institution based on muadalah and is under the auspices of the Al-Amien Prenduan Islamic boarding school. Good classroom management is needed to achieve the objectives. This study aims to determine the implementation of classroom management and to find supporting and inhibiting factors of class management on Islamic Cultural History learning in class 1A TMI Putri Al-Amien Prenduan. This research used a qualitative approach. Researchers collected data by using interviews, observation, and documentation methods. Data sources were obtained from teachers and learners. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. While the technique used to check the validity of the data is the triangulation technique The results of this study showed that: First, the implementation of classroom management on Islamic Cultural History learning in the class of IA TMI Putri Al-Amien Prenduan consisted of planning, implementing, and evaluating went well because the teacher had implemented several existing classroom management principles. Second, the supporting factors and inhibiting factors come from two factors, namely the teacher factor and the student factor.